Games of no chance 6 - Larsson, Urban (Mathematical Sciences Research Institute publications, 2025)
This collection of 22 research papers and state-of-the-art surveys extends the subseries 'Games of No Chance' pioneered in 1996. Survey topics include Richman bidding combinatorial games, classical subtraction games and absolute additive theory. Other topics discussed include extensions of normal play theory such as Absolute CGT and Affine normal play; additive theory; aspects of generic impartial games arising from the study of nim-values; dead-ending misère reduction theorems; Wythoff-type variations; complexity issues; and aspects of classical games including a rigorous justification of the celebrated result that king, bishop and knight can checkmate a lonely king on an arbitrarily large chessboard. The recurring list of open problems, updated and annotated, will interest all practitioners of CGT and related fields including algebra, computer science, combinatorics, number theory and classical game theory